Human Papillomavirus Prevalence in Oral and Oropharyngeal Rinse and Gargle Specimens of Dental Patients and of an HIV-Positive Cohort from Pretoria, South Africa - Neil H. Wood; Koketso S. Makua; Ramokone L. Lebelo; Nina Redzic; Ina Benoy; Olivier M. Vanderveken; Johannes Bogers (Advances in Virology)
Introduction. Studies on HPV prevalence in the head and neck region of South Africans are sparse. Of the available reports in the literature, there were no studies on the association between HPV-DNA presence in the mouth and oropharynx in relation to high-risk behaviours such as oral sex practice or tobacco and alcohol use. Materials and Methods. Following ethical clearance and informed consent, patients attending a regional HIV-management clinic and patients attending a dental hospital were recruited to this study. The participants completed an interview-based questionnaire obtaining demographic information, data on HIV serostatus, and behavioural data including sexual practices and tobacco and alcohol use, and a rinse-and-gargle specimen was taken. Specimens were analysed for HPV DNA on 3 separate PCR/qPCR platforms. Statistical analyses were performed for associations between the study group and categorical variables, HPV status, and data from the questionnaires. Results. Of 221 participants, 149 were from a general population and 72 from the HIV-management clinic. Smokers comprised 29.4% of the sample, and 45.2% of participants reported to have ever used alcohol. Open mouth kissing during teenage years was confirmed by 64.7% of participants, 40.3% have given oral sex with their mouth, and 44.8% confirmed to have received oral sex from their partner’s mouth. Seven participants (3.2%) had detectable α-HPV DNA, and 1 (0.4%) had detectable β-HPV DNA in their rinse-and-gargle specimens. Two participants were from the HIV-management clinic and 6 from the general dental population (overall 3.6%). Conclusion. Five high-risk HPV, 2 low-risk HPV, and one β-HPV types were detected. The low prevalence of 3.6% compares well to similar studies in different cohorts studied in South Africa and falls within the global oral/oropharyngeal prevalence spectrum. Only 4 participants, all from the HIV-management clinic, had palatine tonsils. No significant relationships were found between HPV presence and demographic data or sexual, oral sexual, tobacco use, or alcohol use, and no associations were seen with numbers of sexual and oral-sex partners.